Environmental enrichment does not influence hypersynchronous network activity in the Tg2576 mouse model of Alzheimer’s disease - Bezzina, Charlotte; Verret, Laure; Halley, Hélène; Dahan, Lionel; Rampon, Claire (Frontiers in Aging Neuroscience, 2015)
The cognitive reserve hypothesis claims that the brain can overcome pathology by reinforcing preexistent processes or by developing alternative cognitive strategies. Epidemiological studies have revealed that this reserve can be built throughout life experiences as education or leisure activities. We previously showed that an early transient environmental enrichment durably improves memory performances in the Tg2576 mouse model of Alzheimer’s disease. Recently, we evidenced a hypersynchronous brain network activity in young adult Tg2576 mice. As aberrant oscillatory activity can contribute to memory deficits, we wondered whether the long-lasting memory improvements observed after environmental enrichment were associated with a reduction of neuronal network hypersynchrony. Thus, we exposed non-transgenic and Tg2576 mice to standard or enriched housing conditions for 10 weeks, starting at 3 months of age. Two weeks after environmental enrichment period, Tg2576 mice presented similar seizure susceptibility to a GABA receptor antagonist. Immediately after and two weeks after this enrichment period, standard and enriched-housed Tg2576 mice did not differ with regards to the frequency of interictal spikes on their electroencephalographic recordings. Thus, the long-lasting effect of this environmental enrichment protocol on memory capacities in Tg2576 mice is not mediated by a reduction of their cerebral aberrant neuronal activity at early ages.